Activation of Autophagy Through the NLRP3/mTOR Pathway: A Potential Mechanism for Alleviation of Pneumonia by QingFei Yin - Sun, Xiaozhou; Wang, Dandan; Ding, Lizhong; Xu, Yan; Qi, Wenxiu; Zhao, Daqing; Liu, Li; Yin, Chengcheng; Cui, Changsheng; Wang, Zhongtian; Sun, Liwei; Sun, Liping (Frontiers in Pharmacology, 2022)
QingFei Yin (QFY), a Chinese traditional medicine recipe, is known for its excellent therapeutic efficacy for the treatment of bacterial lung infections, although its molecular mechanism of action remains unknown. Here, QFY chemical composition was determined using the High Performance Liquid Chromatography-Mass (HPLC-MS/MS) method, and then QFY was evaluated for protective efficacy against pneumonia using two models: a Streptococcus pneumoniae-induced in vivo mouse model and an in vitro pneumolysin (PLY)-induced murine lung alveolar-derived MH-S cell line-based model. Notably, QFY exerted prominent anti-pneumonia effects both in vivo and in vitro. To further explore QFY protective effects, 4D Label free proteomics analysis, pathologic evaluation and immunohistochemical (IHC) analysis were conducted to identify pathways involved in QFY protection. Notably, we speculated that NLRP3 and autophagy pathways may be involved in the pharmacological effects for QFY-based protection, with both pathways linked closely to each other. Briefly, QFY triggered autophagy via down-regulation of upstream NLRP3/mTOR signaling pathway events, resulting in of the amelioration of inflammatory injury. Collectively, our results reveal molecular mechanisms underlying QFY protection against pneumonia as a foundation for the future development of novel treatment therapy to combat this disease and reduce antibiotic abuse.